SELEKSI JAMUR ANTAGONIS Aspergillus niger DARI BEBERAPA LAHAN PERKEBUNAN KAKAO UNTUK MENGENDALIKAN Phytophthora palmivora - Dwi Eli Wulandari; Asrul Asrul; Irwan Lakani (Universitas Tadulako, 2016)
Aspergillus niger produces α-amylase and glucoamylase enzymes whichenable starch to be broken down into simple glucose then fermented into ethanol. The growth of A. niger is directly related to food substances within the medium. A. nigeralso generatessuch enzymes as amylase, amyloglucosidase, pectinase, cellulose, glycoside that can break down urea into amino acid and CO2. The research objective was to find A. Niger fungi isolate which potentially has antagonist characters against the growth of P. Palmivora fungi in cacao fruits. The research was conducted in the Pest and Disease Laboratory, Faculty of Agriculture of Tadulako University from September to December 2015. The research results showed that 20 isolates of A. niger found are potentially utilized as biological control agents of fungal antagonist against P. Palmivora in four villages where cacao are produced i.e. Sidondo, Lalundu, Towiora and Martajaya. The results of in-vitro inhibition test suggested that two isolates best in suppressing the growth of P. Palmivora causing cacao fruit rot are Lalundu isolates (rate of inhibition of 63.65%) and Martajaya isolates (rate of inhibition of 63.63%)Key Words: Aspergillus niger, fungi, antagonis, Phytophthora palmivora.